Metabolic regulation of stress erythropoiesis, outstanding questions, and possible paradigms - Ruan, Baiye; Paulson, Robert F. (Frontiers in Physiology, 2023)
Steady state erythropoiesis produces new erythrocytes at a constant rate to replace the senescent cells that are removed by macrophages in the liver and spleen. However, infection and tissue damage disrupt the production of erythrocytes by steady state erythropoiesis. During these times, stress erythropoiesis is induced to compensate for the loss of erythroid output. The strategy of stress erythropoiesis is different than steady state erythropoiesis. Stress erythropoiesis generates a wave of new erythrocytes to maintain homeostasis until steady state conditions are resumed. Stress erythropoiesis relies on the rapid proliferation of immature progenitor cells that do not differentiate until the increase in serum Erythropoietin (Epo) promotes the transition to committed progenitors that enables their synchronous differentiation. Emerging evidence has revealed a central role for cell metabolism in regulating the proliferation and differentiation of stress erythroid progenitors. During the initial expansion stage, the immature progenitors are supported by extensive metabolic changes which are designed to direct the use of glucose and glutamine to increase the biosynthesis of macromolecules necessary for cell growth and division. At the same time, these metabolic changes act to suppress the expression of genes involved in erythroid differentiation. In the subsequent transition stage, changes in niche signals alter progenitor metabolism which in turn removes the inhibition of erythroid differentiation generating a bolus of new erythrocytes to alleviate anemia. This review summarizes what is known about the metabolic regulation of stress erythropoiesis and discusses potential mechanisms for metabolic regulation of proliferation and differentiation.